Horticulture policy for Khyber Pakhtunkhwa - Rana, Abdul Wajid; Raja, Sehrish; Qureshi, Tehseen Ahmed (International Food Policy Research Institute, 2022)
Pakistan’s rich soil and four seasons are favorable for horticulture. The country’s horticultural sector: (a) benefits from favourable and diversified agroecological conditions; (b) geographically and strategically well placed to enhance its exports to highly competitive but lucrative markets like Middle East, Afghanistan, Iran, China, Central Asian Republics, Europe and Far East; and (c) plays a major socioeconomic role in Pakistan, in particular for women’s economic empowerment. While Pakistan is a major producer of horticultural products, its tremendous export potential remains largely untapped. The sector’s structure, the characteristics and varieties of the Fruits and Vegetables (F&V) grown locally, and the way in which F&V are being cultivated, aggregated, and transported have a huge bearing on the sector’s trade performance and have a tremendous impact on its competitiveness. The production base is highly fragmented, with approximately 85% of the orchards having an area of less than 12.5 acres.